Exploring constructivist task motivation of English L2 acquisition graduate students through learning materials - Ngoepe, L.J. (South African Journal of Higher Education, 2019)
English Second Language Acquisition (ESLA) students need relatively more support from their learning environment. This essential support could be in the form of task motivation through L2 materials in their academic endeavour to create knowledge among the English language community mainly consisting of peers and lecturers. In a bid to motivate students to perform planned tasks which eventually lead them to participating in language learning, of their own volition, the lecturer is cognisant of students’ Individual Differences (IDs) and links this to Dynamic Systems (DS) which can play a role in the process of ESLA. The researcher motivated ESLA graduate students to perform tasks through L2 materials.